Active packaging gelatin films based on chitosan/Arabic gum/coconut oil Pickering nano emulsions. Issue 1 (26th July 2021) - Sultan, Maha; Elsayed, Hamed; Abdelhakim, Abou El Fettouh; Taha, Ghada
Abstract: This investigation intended at fabricating gelatin active packaging films based on nano‐sized droplets of coconut oil emulsified by Pickering emulsion (PE) using chitosan/Arabic gum (CH/AG) nanoparticles (NPs) as a stabilizer and in the presence of titanium dioxide NP (TiO2 NPs) as an extra antimicrobial agent. The developed films were characterized by attenuated total reflectance–Fourier transmittance infrared, X‐ray diffraction, and scanning electron microscope. The antimicrobial, antioxidant, water vapor sorption isotherm, and mechanical properties of the prepared films were assessed. The (CH/AG) NPs weight ratios (1:1, 1:2, and 2:1) impact on particle size (PS), zeta potential, wettability, morphology, and in vitro cumulative release was investigated. The (CH/AG) NPs (1:2) exhibits the small PS (246.4 nm). (CH/AG) NPs and PE exhibit spherical and oval morphologies. The CH/AG (1:2) exhibits the higher water contact angle (85.7 o ). At the oil volume fraction ( α ) = 1.0, nearly 81% of the entrapped oil released from the NPs. Gelatin films enriched with P at α = 1.0 exhibits two‐fold increasing scavenging activity % (35.69 ± 0.56) compared with control film (14.8 ± 0.25). The films have a considerable antibacterial and antifungal activity for all test microorganism. However, control sample did not show antimicrobial activity against Bacillus cereus and Candida albicans . Abstract :